Uma análise da previdência social brasileira e os custos da não reforma - Rodrigues, Artur Félix Monteiro (2018)
The Brazilian General Social Security System plays a fundamental paper in the quality of life and development of our society. The focus of this dissertation will be to analyze the impact of the change in the age structure of the Brazilian population on the General Social Security System (RGPS) in face of the current rules for granting benefits. To do so, a diagnosis of the current system is made, observing the demographic data of IBGE, macroeconomic fundamentals and Social Security regarding the main Brazilian social security aspects. It will portray the effect of the demographic changes on RGPS revenues and expenses and developed an analysis of the fiscal effects in relation to GDP and public budget from the projection of RGPS data for the coming decades. Given these results will be shown the growing weight of social security expenditures in relation to GDP and budget, possibly burdening other areas of social interest and suggesting a reform in its structure in the coming years.